Genetics and combining ability of corn (Zea mays L.) genotypes for forage utilization - Abu Sin, Maizura (2019)
Studies were conducted to evaluate agronomic and nutritive quality performance of forage corn inbred lines obtained from the International Wheat and Maize Improvement Center (CIMMYT), with the objectives to reveal genetic variation among these genotypes using simple sequence repeat (SSR) DNA markers, to investigate and select potential parental inbred lines from different heterotic groups based on genetic diversity revealed by agronomic and molecular characteristics towards hybrid variety production, and to determine their heterosis and combining ability, and performance of hybrids produced for forage utilization. In the first study, genetic diversity and relationships among 30 corn inbred lines comprising of 28 introductions from the International Wheat and Maize Improvement Center (CIMMYT), one from Indonesia and a locally developed one, were evaluated using 100 simple sequence repeat (SSR) markers. A total of 550 alleles were detected on 100 loci from the 30 inbred lines. Results showed that allelic richness per locus was in the range of 2 to 13 loci, with an average of 5.50 alleles. From these, the effective alleles (Ne) per locus was estimated at 3.75 alleles, indicating that those alleles were effective in showing diversity among the inbred lines. Although allelic richness among the inbred lines was high, estimate of observed heterozygosity (Ho) was found to be low for each inbred line, with an average of 0.017. This indicates that the inbred lines have reached homozygosity at almost all loci amplified. Polymorphic information content (PIC) values among the 100 loci ranged from 0.178 to 0.874, with mean value of 0.624, showing that the SSR markers used were informative and able to assess genetic diversity among the inbred lines. Four heterotic groups were formed from the dendrogram constructed using Unweighted Pair Group with Arithmetic Averages (UPGMA) method within a similarity index of 0.350. In the second study, 19 diverse homozygous inbred lines representing 28 inbred lines from the first study were evaluated under optimum conditions, and were found to show significant differences in performance of the traits among them, indicating that the lines varied in many aspects, and these differences could be exploited for specific purposes in breeding programs. Genetic distances among the inbred lines based on phenotypic and molecular characteristics were used to identify major heterotic groups and have revealed the presence of high level of genetic diversity among the inbred lines studied. Selection of the parental inbred lines among the genetically diverse ones for making crosses was conducted based on their performance for important forage traits. In the third study, six parental inbred lines were selected and crossed in a half-diallel arrangement to produce 15 single-cross hybrids. Fifteen single-cross hybrids and their parental inbred lines were evaluated in a randomized complete block design (RCBD) with three replications at two different environments, for agronomic and forage nutritive quality performances. All hybrids showed superiority over their parental inbred lines for biomass traits studied, indicating the existence of a substantial amount of heterosis in the hybrids. Among the hybrids produced, HF10, HF3, HF15, HF1 HF13 and HF11 revealed forage yield, forage yield components and forage nutritive quality performance better than the check varieties (BTL1 and Pool26) in the two environments studied. Moreover, these hybrids exhibited consistently high mid-parent and better-parent heterosis for the traits studied, indicating the accumulation of favorable genes inherited from their parental inbred lines. Mid-parent and better-parent heterosis estimates revealed from the evaluations were positive for all traits except acid detergent fiber (ADF), neutral detergent fiber (NDF), days to tasseling and days to silking, where the lower magnitudes of these traits were superior, indicating earliness. The combining ability analysis reveals the presence of significant general combining ability (GCA) for all traits except dry leaf yield, dry ear yield and ADF, and the presence of significant specific combining ability (SCA) for all traits except NDF, days to silking and days to tasseling from the combined data of the two environments. This indicates that there were significant additive and non-additive gene actions involved in the genetic control of the traits measured from the combined data of the two environments. Inbred line CML428 was identified as the best general combiner among the parental inbred lines and performed consistently, with significant GCA estimates for fresh plant yield, dry plant yield, fresh stem yield, dry stem yield, plant height and ear height, and was therefore identified as the superior one possessing high accumulation of favorable additive genes. In addition, high negative estimates of GCA were found contributing to early days to flowering of the progeny. Among the crosses, HF9 (CML331 x CML498), HF6 (CML331 x CML383), HF11 (CML383 x CML491) and HF10 (CML383 x CML428) were identified as the best combinations giving favorable positive SCA estimates for forage yield and yield related traits at each environment and pooled environments. In general, fresh and dry matter yields exhibited low narrow-sense heritability although having high broad-sense heritability, indicating the preponderance of non-additive gene actions in the inheritance of the yield traits measured. Based on genetic similarities among the parental inbred lines, when data were taken from amplifications of microsatellite markers with more than 30% polymorphic bands, CML491 and CML498 were found to reveal the highest genetic similarity (0.410), while CML383 and CML428 were found to exhibit the lowest genetic similarity (0.149). The low genetic similarity could indicate diverse genetic background among the inbred lines, due to prior selection applied on the parental inbred lines from different heterotic groups. The combination of CML383 x CML428 (HF10) was identified among those with high yield and good nutritive quality performance. In addition, this combination was one of the best, with favorable positive SCA estimates for forage yield and yield related traits at each environment and pooled environments. There were significant positive relationships between genetic similarities of parental inbred lines based on 100 microsatellite markers used and mid-parent heterosis for fresh plant yield, and between genetic similarities of parental inbred lines based on microsatellite markers with more than 30% polymorphic bands and mid-parent heterosis for fresh plant yield in Field 10 and also when data of the two environments were combined. This reveals the effectiveness of the markers used in this study for prediction of performance of hybrids produced for forage utilization. The performance of these superior hybrids was consistent across environments, and therefore these hybrids should be considered for further testing in multi-locational trials to reveal their potential, before their release as new forage corn hybrid varieties in the future.